2022
DOI: 10.1007/s00423-022-02464-1
|View full text |Cite
|
Sign up to set email alerts
|

Early elective versus elective sigmoid resection in diverticular disease: not only timing matters—a single institutional retrospective review of 133 patients

Abstract: Purpose The optimal timing of elective surgery in patients with the colonic diverticular disease remains controversial. We aimed to analyze the timing of sigmoidectomy in patients with diverticular disease and its influence on postoperative course with respect to the classification of diverticular disease (CDD). Methods Patients who underwent elective laparoscopic sigmoidectomy were retrospectively enrolled and subdivided into two groups based on the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Elective surgery was performed either within 6 weeks after the acute attack (early elective) or after 6 weeks in the inflammation-free interval (delayed elective) The surgical approach (open vs. laparoscopic) was primarily determined based on the severity of the diverticular disease stage, the clinical condition of the patient and contraindications of laparoscopic surgery and secondly at the discretion of the involved surgeon. The technique of laparoscopic sigmoid resection was described in our previous study [26]. Patients with fecal or purulent contamination and severe sepsis underwent damage control sigmoidectomy and subsequent second or third look procedures if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Elective surgery was performed either within 6 weeks after the acute attack (early elective) or after 6 weeks in the inflammation-free interval (delayed elective) The surgical approach (open vs. laparoscopic) was primarily determined based on the severity of the diverticular disease stage, the clinical condition of the patient and contraindications of laparoscopic surgery and secondly at the discretion of the involved surgeon. The technique of laparoscopic sigmoid resection was described in our previous study [26]. Patients with fecal or purulent contamination and severe sepsis underwent damage control sigmoidectomy and subsequent second or third look procedures if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…The initial database research with the previously defined keywords identified 2347 potentially relevant abstracts. Of these, 17 full-text articles were assessed for eligibility and finally, 11 studies (8 retrospective and 3 prospective non-randomized cohort studies) comparing the outcome of operative timing in sigmoid diverticular disease were included in the qualitative and quantitative data analysis [26][27][28][29][30][31][32][33][34][35][36]. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram for the literature search is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the distribution of sigmoid diverticular disease stages throughout the analyzed studies is not homogenous. While some authors [33,34] exclude cases with complicated disease stages, others [28,[30][31][32]36] mixed cases with chronic or complicated and noncomplicated sigmoid diverticulitis. The hereby presented results must be cautiously interpreted as all the included and analyzed studies are nonrandomized with the limited methodical quality attributed to observational cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations